Game development with Construct 2 : from design to realization - Stemkoski, Lee; Leider, Evan (Apress, 2017)
Design and create video games using Construct 2. No prior experience is required. Game Development with Construct 2 teaches you to create 12 different game projects from a variety of genres, including car racing and tower defense to platformer and action-adventure. The software is user friendly and powerful, and the games you create can be exported to run on the web, desktop computers, and smartphones. What You'll Learn Create complete functional games using the Construct 2 game engine Understand general logical structures underlying video game programs Use practical game design advice (such as visual feedback and gameplay balancing) Understand programming concepts useful throughout computer science.